The Marginalia of Pope Alexander VII in a Vatican Copy of the Hypnerotomachia Poliphili - James Russell (Ceræ)
Pope Alexander VII (Fabio Chigi, 1599–1667) extensively annotated a copy of the 1499 incunable Hypnerotomachia Poliphili (hereafter ‘HP’), printed by Aldus Manutius, which is in the Biblioteca Apostolica Vaticana. The HP, an architectural dream narrative crossed with an encyclopedia, has attracted scholarly attention primarily due to its elaborate architectural woodcuts and to speculation as to the identity of its anonymous author. This study reorients the focus towards its readership, reframing the HP as a used text as evidenced by the Pope’s marginalia. Prior studies have noted the resemblance of a woodcut of an elephant-and-obelisk in the HP to the last sculpture by Bernini in Chigi’s lifetime, outside Santa Maria sopra Minerva. This paper, the first extended study of Chigi’s marginalia, shows that the Pope’s engagement with the HP went beyond this one sculpture. Chigi thought of his journey through the architectural dreamspace by analogy with his own actual progresses through Baroque Rome under construction. The Pope marked the locations of characters and objects within the HP’s three-dimensional diegetic space. Moreover, Chigi also took interest in the rhetorical structure of the HP’s descriptions of its visual marvels, drawing on the traditions of imprese and acutezze.